KUALITAS PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BENGKULU TENGAH - Antonio Imanda (UNIVED PRESS, Universitas Dehasen Bengkulu, 2014)
Public service is a very crucial and interesting issue to discuss because it always exists in a state where the state and the administration stands. The implementation of public service is still far from the ideal expectation of the public. The identification of the unexpected services is visible in terms of the waiting and public services which often face uncertainly. It is very difficult to estimate when the services can be obtained, and on the other side it sometimes needs some unofficially fee to undergo the process of getting the services. This research aims to find out the quality of public services at the office of population and civil registry in Bengkulu Tengah regency. This research uses a descriptive qualitative approach. The data used in this research is secondary and primary data. In the data collection, the researcher uses triangulation technique and the researcher uses informants by purposive sampling technique. The data process and analysis were carried out by means of data reduction, presentation, and making conclusion. From the research results and discussion, the poor quality of public services in Bengkulu Tengah was caused by; 1) low level of consistency between the waiting time and the processing time, 2) common mistakes about the accuracy of the services especially regarding errors in the printing of the document, 3) lack of courtesy and hospitality of the employees as well as lack of mutual respect of the clerk, 4) the employees have weak sense of responsibility in providing services, especially regarding discipline employees, 5) the administration wares of making identity cards shows that it is easier to get, but it is different from the wares of making the family cards, in which it shows some more difficult, 6) it is still rather difficult to get the services, the frequent discriminatory attitudes, the lack amount of employees, and moreover the wares such as computer and other facilities are still limited, 7) no variation of service model, 8) the low level of personal services provided by the officers, 9) there is no comfort in obtaining the services, 10) the unavailability of supporting facilities, clean environment and enjoyable circumstance. Then, the environment also has lack of regularity, neatness, tidiness and cleanliness. Based on the conclusion above, the government should develop the human resources in both the quantity and the quality in order to be able to improve the services including the employees’ discipline enforcement, improving apparatus’ mental through the provision of punishment and reward, and structured of the standard of procedure operational, the increase in the means of supporting driven computerized technologies and a more adequate office lies in a strategic area and circumstance.Keywords : quality of public services, civil registry